TANGGUNG JAWAB HUKUM DOKTER YANG MELAKUKAN PRAKTIK KEDOKTERAN TANPA MEMILIKI SURAT IZIN PRAKTIK DIHUBUNGKAN UNDANG-UNDANG NO.29 TAHUN 2004 TENTANG PRAKTIK KEDOKTERAN DAN ASAS KEPASTIAN HUKUM - Meifiyane Angmawaty Fadlillah (Iustitia Omnibus (Jurnal Ilmu Hukum), 2022)
The last twenty years have often arisen lawsuits from patients and families who feel aggrieved, to demand compensation due to mistakes or omissions made by doctors or medical personnel in carrying out their work. This situation shows a symptom, that the world of medicine is being hit by a medical ethics crisis that cannot be resolved by a medical code of ethics alone, but must be resolved in a broader way that must be resolved through legal channels.The purpose of the study is to Know, Analyze and Describe the Responsibility of Criminal Law towards Doctors Who Practice Medicine Without Having a License to Practice connected with Law No.29 of 2004 concerning the practice of medicine and the principle of legal certainty and Knowing, analyzing and describing the Obstacles that occur in legal enforcement against Doctors who do not have a License to Practice and their Solutions The method used in writing this thesis uses a normative legal approach (normative juridical) with data collection techniques, namely library research (library reseach) which focuses on secondary data.A doctor can be said to be negligent in carrying out medical actions if in carrying out his duties as a health servant is not in accordance with professional standards and standard operating procedures and the doctor does not act reasonably and carefully and results in defects / injuries and even death to other people (Patients). Based on three decisions, namely the District Court Decision, cassation decision and the Judicial Review Decision The protection that can be applied to doctors who make decisions on medical actions that can result in the death of the patient is if the doctor has worked in accordance with professional standards and standard operating procedures cannot be accounted for by the doctor